Konsep Masyiatullah dalam Proses Pendidikan Islam - Shalahudin Ismail; Ma’mun Zahrudin; Andewi Suhartini (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
The purpose of this study was determining the ‘masyiatullah’ concept in Islamic education process. The approach in this study used a qualitative approach, an approach in natural objects condition, where researchers become key instruments. The results showed that masyiatullah concept was the core of Islamic education, where the concept become a solid foundation to form students who believe and have faith. Ideally, Islamic education theology can produce a generation who had the awareness that they are servants of God.